2017 ACC/AHA/HRS Guideline for the Evaluation and Management of Patients With Syncope: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines and the Heart Rhythm Society. Issue 5 (1st August 2017) - Shen, Win-Kuang; Sheldon, Robert S.; Benditt, David G.; Cohen, Mitchell I.; Forman, Daniel E.; Goldberger, Zachary D.; Grubb, Blair P.; Hamdan, Mohamed H.; Krahn, Andrew D.; Link, Mark S.; Olshansky, Brian; Raj, Satish R.; et al.
Abstract : Supplemental Digital Content is available in the text.